ChemInform Abstract: High Nuclearity Antimonato‐Polyoxovanadate Cluster V15Sb6O42 as a Synthon for the Solvothermal in situ Generation of α‐ and β‐V14Sb8O42 Isomers. Issue 36 (August 2016) - Wendt, Michael; Naether, Christian; Bensch, Wolfgang
Abstract: The high‐nuclearity cluster compound (I) is shown to be an excellent new synthon for the preparation of (II) containing the β‐V14 Sb8 O42 isomer and the new compound (V) containing the α‐V14 Sb8 O42 isomer.